A modernização dos serviços urbanos de abastecimento d’água na São Luís Oitocentista, advinda das viagens de estudos de jovens maranhenses para a Europa: caso da Companhia Anil - PINHEIRO, Luiz Antonio (2017)
The urban evolution of the city of São Luís, capital of the state of Maranhão, recorded social and urban transformations in the nineteenth century, operating in sectors of education, health, agriculture, communication, industry and urbanism as a result of the performance of young maranhenses graduated in European Universities. Among the urban interventions to reshape the public addresses and ensure the quality of life of the city dwellers, the water supply system is addressed in a period in which few households had their own drinking water and the vast majority was supplied through the Public sources and the system of water sales, door to door, with the use of carts with wooden barrels. The ideas brought from the European continent by the young engineer graduated at the École des Ponts et Chaussées, in Paris, confronted the model of supply used, to implement a mechanical system of watering, treatment and distribution in the streets and Ludovicense residences, which was the object of strong rejection by the owners of the "companies" of water sales which used to have as representatives Ana Jansen Pereira and Cunha Santos. In this present study, the processes of transformation then recorded in São Luís are analyzed, especially the proposed water supply system and implemented by Raimundo Teixeira Mendes, aiming at bringing up new reflections on the transformations which occurred in the city in the second half of the 800's, when the flow of maranhenses went and studied in the European capitals increased and it "broke" the hegemony of Coimbra as the only destination of the maranhenses to get a higher education. This survey has two crucial points of analysis: the condition of São Luís behind the Brazilian Athenas; And the Anil Company, responsible for the canalization of the waters of the Anil River for the supply of the city with the trailing and mishaps arising from the strong opposition made by the owners of the old water supply companies of the city, since the eighteenth century. As a source of research, the documents of the Anil company, the Senate of the House of São Luís, in addition to the periodicals circulating during that period, classical works of Maranhão historiography, and the contemporary authors who study the eighteenth century social history, were primarily used.